DRAMATIC READING OF THE TEXT OF PLAY SCRIPT THROUGH AUDIO RECORDING - Hasan Hasan; Nugroho Notosutanto Arhon Dhony (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
Media of audio recording can be made as the media of learning, whether it's done in the class or outside the class such as study group. Using audio recording in smart phone or hand phone enables the learning of practical tutorial model, and one of them is the learning material of theater art. For art teacher in the school particularly theater teacher, it's very difficult for students to memorize the play script in role playing. When art teacher gives realism play script, main thing responded by students is the difficulty of memorizing the scripts because these scripts written by authors that are very familiar with theater world are full of meaningful literary words. Teacher or trainer reads the script dramatically (dramatic reading while recording). From dramatic reading, it's seen the plot of script dramatically and described the atmosphere in the script wholly. Teacher or trainer hands out recording result to students or actors via WhatsApp, Line, and other applications of social media and students can read the script while listening for the result of teacher's or trainer's recording. Memorizing process will be faster if the students listen to the recording by using handset. Utilizing technology can facilitate theater exercise.